Persons with Alzheimer's disease engage in leisure and mild physical activity with the support of technology-aided programs. (February 2015) - Lancioni, Giulio E.; Singh, Nirbhay N.; O'Reilly, Mark F.; Sigafoos, Jeff; D'Amico, Fiora; Sasanelli, Giovanni; De Vanna, Floriana; Signorino, Mario
Highlights: Three computer-aided programs were used with patients with mild to severe Alzheimer's disease. In Study I, the program was aimed at helping three patients to choose among music options. In Study II, the program was aimed at helping three patients exercise an arm-raising movement. In Study III, the program was aimed at helping three patients exercise a leg-foot movement. All three programs produced satisfactory results. Abstract: Three studies were conducted to assess technology-aided programs to promote leisure engagement and mild physical activity in persons with Alzheimer's disease. Specifically, Study I assessed a program aimed at enabling three patients with mild or moderate Alzheimer's disease to choose among different music options and activate the preferred ones. Studies II and III were directed at patients in the low moderate or severe stages of the Alzheimer's disease who were no longer capable of ambulating and spent their time generally inactive, sitting in their wheelchairs. In particular, Study II used a program to help three patients exercise an arm-raising movement. Study III used a program to help three patients exercise a leg-foot movement. Each study was carried out according to a nonconcurrent multiple baseline design across patients. Results were very encouraging. The patients of Study I learned to choose and activate their preferred music pieces. The patients of Studies II and III enhanced their performance of the target movements and increased their indices of positive participation (e.g., smiles and verbalizations) during the sessions. The applicability of the programs in daily contexts and their implications for the patients involved are discussed.